Instructional Advice and Information Providing and Receiving Behavior in Elementary Schools: Exploring Tie Formation as a Building Block in Social Capital Development - Spillane, James P.; Kim, Chong Min; Frank, Kenneth A. (American educational research journal, 2012)
Few studies identify those factors that might account for the development of social capital. Understanding those factors associated with the existence of a social tie among actors in schools is important because absent social ties, individuals do not have access to social resources. We investigate social tie formation in schools focusing on advice and information providing and receiving in the two core elementary school subjects. Using a multilevel p 2 model, we examine the role of both formal organizational structure and individual characteristics in shaping advice and information providing and receiving about instruction. Our findings suggest that while the individual characteristics of race and gender are significantly associated with the formation of a tie, aspects of the formal school organization—grade-level assignment, having a formally designated leadership position, and teaching a single grade—are also significant and have larger estimated effects than individual characteristics. Formal organizational factors trump individual characteristics in the formation of a social tie, a necessary if insufficient condition for social capital development.